2009
DOI: 10.1188/09.onf.e153-e158
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Perceptions of Quality of Life of Breast Cancer Survivors and Their Male Partners

Abstract: Partners' judgments of patients' QOL may be important in some circumstances, particularly when patients are not able to answer questions about their own QOL because of cognitive or functional limitations. Nurses must be aware that partners are the most frequent informal caregivers and should be included in the entire treatment process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…However, their range of 1-56% prevalence of depression was wider than we found (3.0-41.7%). In Zainal's review, the three studies with the highest prevalence also included patients in their first year after diagnosis [36][37][38]. It is known that the prevalence of depression is high during the first year after breast cancer diagnosis [39].…”
Section: Results In Relation To Other Resultsmentioning
confidence: 98%
“…However, their range of 1-56% prevalence of depression was wider than we found (3.0-41.7%). In Zainal's review, the three studies with the highest prevalence also included patients in their first year after diagnosis [36][37][38]. It is known that the prevalence of depression is high during the first year after breast cancer diagnosis [39].…”
Section: Results In Relation To Other Resultsmentioning
confidence: 98%
“…However, in this study, we found that this situation blocked the opportunity for understanding between the couple, and affected their communication through language. Rabin et al (2009) found that the spouse of cancer patient know his partner's condition very well, especially on her quality of life. However, the results of this study showed that the husbands did not think they could understand how their wives thought.…”
Section: Discussionmentioning
confidence: 98%
“…Moderate to high distress is typically reported in the immediate aftermath of diagnosis and treatment, followed by a gradual reduction over the following year or two (Kayser & Scott, 2008;Meyerowitz & Oh, 2009;Rabin et al, 2009). However, a significant portion of patients continue to experience psychological distress well into survivorship.…”
mentioning
confidence: 97%
“…icant anxiety and up to half experiencing depression (Meyerowitz & Oh, 2009;National Breast Cancer Centre, 2003;Rabin et al, 2009). Moderate to high distress is typically reported in the immediate aftermath of diagnosis and treatment, followed by a gradual reduction over the following year or two (Kayser & Scott, 2008;Meyerowitz & Oh, 2009;Rabin et al, 2009).…”
mentioning
confidence: 97%